The ultimate guide to compact cases : case research, writing, and teaching - Morris, Rebecca J. (Emerald Publishing Limited, 2022)
This ultimate guide focuses on case research, writing, and teaching for a revolutionary new form of teaching case--Compact Cases. Designed to be read in 15 minutes or less, Compact Cases provide a more engaging learning experience for today's students. Compact Cases overcome students' lack of preparation for case discussions by making cases more accessible, readable and engaging. Whether students read a Compact Case before class or in class, better learning outcomes can be achieved by actively engaging students in case analysis and discussion. Annotated cases, examples from published cases, helpful checklists, roadmaps, and writing prompts are provided to assist others in mastering the writing of short teaching cases and the accompanying teaching notes. Readers will learn to identify suitable case topics, develop effective learning objectives, use appropriate research methodologies, write lively and short prose, create more engaging exhibits, and prepare value-added teaching notes. Teaching strategies for effectively using Compact Cases online, in person, or blended teaching modes are provided. Strategies for publishing cases are provided to help case writers successfully share their work with others. Novice and experienced case writers will find tips, ideas, and strategies to improve student learning by using and writing Compact Cases.